(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Organizational effectiveness has been regarded as a vital factor of success in organizations. Especially, in the school system, the principals’ leadership and teachers’ perception of empowerment have been reported as the important variables affecting organizational effectiveness (Sin, 2008). However, few study has investigated organizational effectiveness and related factors in the setting of early childhood education in South Korea. Therefore, we examined the effects of principals’ emotional leadership and early childhood teachers’ empowerment on organizational effectiveness in kindergartens and childcare centers in South Korea. The sample comprised 250 early childhood teachers in South Korea. The empirical data were collected by administering the Organizational Effectiveness Scale for Early Childhood Teachers (Lee, 2016), Emotional Leadership Scale for Early Educational Program Directors (Kwon & Kim, 2014), and School Participant Empowerment Scale (Short & Rinehart, 1992). The collected data were analysed using SPSS 22.0 with the descriptive statistics, Pearson’s correlation analysis, and the analysis of multiple regression. The results revealed that principals’ emotional leadership and early childhood teachers’ empowerment positively affected organizational effectiveness in the setting of early childhood education in South Korea. Moreover, teachers’ empowerment had more impact than principal’s emotional leadership on organizational effectiveness. The finding of this study suggest that principals’ emotional leadership and early childhood teachers’ empowerment should be improved to increase organizational effectiveness in early childhood educational institutions.